ANALYSIS OF FACTORS AFFECTING LOAN TO DEPOSIT RATIO BPR IN BADUNG DISTRICT - Maha Yoga, Gede Agus Dian; Bendesa, I K G; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
Research purposes 1) analyze the direct influence of internal factors, and external to credit strategy, 2) analyze the direct influence of internal factors, external factors and crediting strategies to LDR, 3) analyze the indirect influence between internal and external factors on LDR crediting strategies as mediators. The research was conducted in Badung regency, using combination of primary and secondary data. Using sample population techniques, Partial Least Square (PLS) is a data analysis technique used. Research result 1) the direct internal factors and external factors have a significant positive effect on the lending strategy, 2) the internal factors directly and the lending strategy have a positive significant effect while the external factors have positive but not significant effect on the LDR, 3) the internal factors and external factors indirectly affect the LDR through crediting strategy as a significant mediator in rural banks in Badung regency